Design of mechatronic workbench using PLC / Mohd Hazizi Haji Zainudin - Zainudin, Mohd Hazizi (Faculty of Mechanical Engineering, 1998)
This project entitled ’Design of Mechatronic Workbench Using PLC' involves a study of PLC. All the equipment needed to achieve the objective of this project are available in Industrial Automation Laboratory. The equipment are a PLC which acts as a control device and pneumatic elements such as air compressor, service unit ( air regulator, air filter and air lubricator), valves, cylinders etc. The air compressor is used to supply compressed air to activate the valves and cylinders. The PLC is used as a control device to control the sequence movement of cylinders based on what we programmed on it.